Desenvolvimento farmacotécnico e atividade antimicrobiana e antioxidante de gel de carbômero contendo extrato de casca de Punica granatum para uso em lesões cutâneas em cães - Silva, Thais Martins da (2021)
The peel is one of the biowaste of pomegranate s fruits formed after the extract of the juice, with the potential to be converted into products with added value for many applications, including the pharmaceutical. The purpose of this present work was to p